Application of QPPO/PVA based commercial anion exchange membrane as an outstanding adsorbent for the removal of Eosin-B dye from wastewaters. (April 2023) - Khan, Muhammad Imran; Shanableh, Abdallah; Alfantazi, Akram M.; Lashari, Mushtaq Hussain; Manzoor, Suryyia; Anwer, Ramsha; Farooq, Nosheen; Harraz, Farid A.; Alsaiari, Mabkhoot; Faisal, M.
Abstract: Commercially available QPPO/PVA based anion exchange membrane (AEM) BIII was to inquire the percentage discharge of anionic dye Eosin-B (EB) at terrain temperature from wastewater. The impact of EB initial concentration, membrane dosage, ionic strength, contact time and temperature on EB percentage removal was contemplated. The EB percentage removal was increased from 22 to 99.56% and 38.15–99.56% with contact time and membrane dosage respectively while decreased from 99.56 to 29%, 99.56 to 54.61% and 99.56 to 92.22% with enhancing initial concentration of EB, ionic strength and temperature respectively. Nonlinear isotherm models were utilized to demonstrate EB adsorption onto AEM BIII. Attained results exhibited that nonliner Freundlich isotherm model best fitted to EB adsorption onto AEM BIII. For EB adsorption onto AEM BIII, adsorption kinetics were inquired in detail by using several kinetic models but EB adsorption nicely fitted to pseudo-second-order kinetics. Similarly thermodynamic analysis was performed and results pointed to an exothermic adsorption of EB onto AEM BIII. The membrane could be reused for four concecutive cycles with loosing its efficiency. Graphical abstract: Image 1 Highlights: QPPO/PVA based commercial anion exchange membrane. exothermic adsorption of EB onto AEM BIII. A novel membrane against absorption of EB. Nonlinear isotherm models were utilized to demonstrate EB adsorption.